INFESTATION OF MAJOR PESTS AND DISEASES ON VARIOUS CASSAVA CLONES IN LAMPUNG-INDONESIA - Swibawa, I Gede; Susilo, Franciscus Xaverius; ., Purnomo; Aeny, Titik Nur; Utomo, Setyo Dwi; Yuliadi, Erwin (Universitas Lampung, 2020)
Infestation of major pests and diseases on various cassava clones in Lampung-Indonesia. Lampung Province is one ofcassava producers in Indonesia which contributes more than 30% to the total national cassava production. However, theinfestation of pests and diseases can limit cassava production in the field. The objective of this research was to observe theinfestation level of major plant pests and diseases of cassava in Lampung. A survey was conducted in August 2016 in severallocations of cassava fields owned by farmers and experimental plots in the area of Faculty of Agriculture, University ofLampung. The results showed that cassava mealybug (Phenacoccus manihoti), papaya mealybug (Paracoccus marginatus)and red mite (Tetranychus urticae) infested at cassava clones in Lampung. The infestation of red mite tended to be higher thanthat of mealybugs. The cassava brown leaf spot disease that infested in mild to moderate severity was found on all cassavaclones, while viral disease with prevalence of 78% was only found on Duwet 1 clone in experimental plot.